Symptom Resolution in Patients with Mycoplasma pneumoniae Pneumonia - Thomas J Marrie; Michael Beecroft; Zeljka Herman-Gnjidic; Melanie Poulin-Costello (Canadian Respiratory Journal)
BACKGROUND: Mycoplasma pneumoniae generally causes pneumonia of mild to moderate severity in adults. However, little is known about the time course of the resolution of symptoms in this illness.